2018
DOI: 10.21615/cesmvz.13.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Resistencia antimicrobiana de Streptococcus agalactiae de origen humano y bovino

Abstract: Artículo de revisión Antimicrobial resistance of Streptococcus agalactiae of human and bovine origin Resistencia antimicrobiana de Streptococcus agalactiae de origen humano y bovinoResistência antimicrobiana de Streptococcus agalactiae de origem humana e bovina

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 58 publications
(93 reference statements)
0
6
0
6
Order By: Relevance
“…Unique identifiers (e.g., P2_4) were assigned to quotes from participating farmers with the first number representing the participant id within the focus group (1)(2)(3)(4)(5)(6)(7)(8) and the second number representing the session (1-7). Square brackets (i.e., [.…”
Section: Discussionmentioning
confidence: 99%
“…Unique identifiers (e.g., P2_4) were assigned to quotes from participating farmers with the first number representing the participant id within the focus group (1)(2)(3)(4)(5)(6)(7)(8) and the second number representing the session (1-7). Square brackets (i.e., [.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the high importance of GBS as an animal pathogen, involved in several pathologies in different hosts, S. agalactiae also has high importance in public health. High resistance levels have been demonstrated in strains isolated from human beings (Botelho et al, 2018;Jaramillo-Jaramillo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This creates the risk of the inefficacy of the treatment protocols for animal and human infections caused by this pathogen. Futhermore, the occurrence of multidrug resistance (MDR) strains of GBS among animals, especially in fish and cattle, increases the threats to human health by the occurrence of interspecies infection, as pointed out in several studies (Botelho et al, 2018;Jaramillo-Jaramillo et al, 2018), and the risk of horizontal transference of resistance genes among GBS of animal and human sources (Pinto et al, 2014). In our study, we found two MDR strains, one of which is resistant to seven classes of antimicrobials, which highlights the need for surveillance over the emergence of MDR S. agalactiae among animal strains.…”
Section: Discussionmentioning
confidence: 99%
“…In GBS, tetracycline resistance is primarily due to ribosomal protection and encoded by tet (M) or tet (O) 56 . In our study, tet (M) was the most common resistance gene in human and bovine isolates.…”
Section: Discussionmentioning
confidence: 99%